Heart Rate Recovery (HRR%) Variation by Position and Measurement Time After Imitation Sparring in Male Jiu-Jitsu Trainees with White Belt - Chul Yoon; Jae-Woong Yang (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
This study measured the physiological response caused by the attack and defence of the top and bottom positions in the Jiu-jitsu game with heart rate to investigate the recovery trend between each position using heart rate recovery (%). The subjects of this study were eight white belt men with more than one year of training experience in the adult division of the Jujitsu competition (from 19 to 29 years). Four teams, each consisting of two people, were selected and experimented by cross-allocation. The sparring was performed in three rounds of five minutes, assuming the competition and the rest time was applied the same as the sparring time. Each position's heart rate recovery rate (%) measurement was based on the heart rate level just before each round. The heart rate of thirty seconds, one, two, three, four, and five minutes immediately after each round (sparring) was measured and expressed in %. The results are as follows: First, the heart rate level immediately after sparring between positions showed a high heart rate level in the bottom position immediately after all rounds (sparring). Second, it was found that the bottom position performed exercise under higher physiological conditions than the top position, and the heart rate recovery tended to rapidly decrease in the bottom position at the same rest time. Third, resting heart rate appears to predict heart rate recovery.